2016
DOI: 10.1039/c6ay00232c
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic fingerprint analysis of Dendrobium huoshanense by ultra-high performance liquid chromatography-electrospray ionization-tandem mass spectrometry

Abstract: A new method for the quality control of genuine Dendrobium huoshanense, which is rare and costly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Although nine flavonoids in D. huoshanense were identified using a UHPLC‐ESI‐MS n method in our previous study , these compounds were not sufficient for the quality control of D. huoshanense . Therefore, in this study, we identified additional flavonoids and identified components specific to D. huoshanense by TLC, HPLC and HPLC–ESI‐MS n .…”
Section: Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…Although nine flavonoids in D. huoshanense were identified using a UHPLC‐ESI‐MS n method in our previous study , these compounds were not sufficient for the quality control of D. huoshanense . Therefore, in this study, we identified additional flavonoids and identified components specific to D. huoshanense by TLC, HPLC and HPLC–ESI‐MS n .…”
Section: Resultsmentioning
confidence: 80%
“…officinale from Zhejiang province and found that they mainly contain flavonoid C‐glycosides. Additionally, our studies on D. officinale stems and leaves showed that D. officinale could be classified into three categories based on the flavonoids present . Chang et al.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations